2019 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2019
DOI: 10.1109/bibm47256.2019.8983138
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Health Coaching Dialogues for Behavioral Goal Extraction

Abstract: Health coaching has been identified as a successful method for motivating and maintaining health behavior changes. Unfortunately, personal health coaching is time-and resourceintensive, and cannot scale up. Previous research focuses on developing conversational systems that can provide automated coaching to patients. But most of these systems rely on a predefined set of input/output mappings, focus more on general goal setting, and do not provide follow-up during goal implementation. Therefore, my research con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 139 publications
(199 reference statements)
0
3
0
Order By: Relevance
“…The remaining remotely delivered interventions commonly apply ML and NLP, potentially indicating the suitability of ML and NLP for use in remote pediatric rehabilitation interventions using AI. ML and NLP have been used in a range of health interventions to promote behavioral changes, such as physical activity and healthy diet, including goal-setting [ 136 , 137 ]. Given the existing evidence on the use of AI for goal-setting in other health care domains [ 136 , 137 ] and the importance of gaining efficiency in enacting the complex process of goal-setting in pediatric rehabilitation [ 138 , 139 ], the lack of attention to goal-setting in this review indicates a clear knowledge gap warranting future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining remotely delivered interventions commonly apply ML and NLP, potentially indicating the suitability of ML and NLP for use in remote pediatric rehabilitation interventions using AI. ML and NLP have been used in a range of health interventions to promote behavioral changes, such as physical activity and healthy diet, including goal-setting [ 136 , 137 ]. Given the existing evidence on the use of AI for goal-setting in other health care domains [ 136 , 137 ] and the importance of gaining efficiency in enacting the complex process of goal-setting in pediatric rehabilitation [ 138 , 139 ], the lack of attention to goal-setting in this review indicates a clear knowledge gap warranting future research.…”
Section: Discussionmentioning
confidence: 99%
“…ML and NLP have been used in a range of health interventions to promote behavioral changes, such as physical activity and healthy diet, including goal-setting [ 136 , 137 ]. Given the existing evidence on the use of AI for goal-setting in other health care domains [ 136 , 137 ] and the importance of gaining efficiency in enacting the complex process of goal-setting in pediatric rehabilitation [ 138 , 139 ], the lack of attention to goal-setting in this review indicates a clear knowledge gap warranting future research. Emerging electronic participation–focused interventions such as the Participation and Environment Measure–Plus [ 140 - 143 ] with individual goal-setting as an integral part of their intervention might benefit from exploring the use of AI to fill this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the type of issue faced during the intervention period, we learned a single strategy that helped to address most of the challenges during the intervention delivery: devoting time to in-person intervention meetings or placing telephone calls when necessary to discuss potential challenges or issues associated with the use of Fitbit. Across the studies we conducted, we dedicated a portion of the in-person meeting to Fitbit-related content [ 9 , 10 , 20 , 35 ]. During this time, participants were free to externalize any concerns or issues related to Fitbit use, and research staff were ready to assist with possible problems or questions.…”
Section: Challenges For Fitbit Use In Interventions and Potential Strmentioning
confidence: 99%
“…We decided to use the CRF model with an F1 macro score of 0.81. In our previous work (Gupta et al, 2020b), we used models with word2vec embeddings (Mikolov et al, 2013) but found ELMo embeddings to perform better.…”
Section: Modeling Smart Attributesmentioning
confidence: 99%
“…We previously showed in Gupta et al (2020b) that metrics like BLEU (Papineni et al, 2002) and ROUGE (Lin, 2004) are not appropriate for our extraction-based goal summaries as they are sensitive to exact word match (Reiter, 2018). That is, if a given word, say 'two', is classified as days number instead of distance, they will still output a high score as 'two' is in the reference summary.…”
Section: Extracting the Goal Summarymentioning
confidence: 99%